Isolation of mycobacterium-reactive CD1-restricted T cells from patients with human immunodeficiency virus infection. - Gong, J (1998)
Because CD1-restricted T cells lack CD4 but produce IFN-gamma in response to nonpeptide mycobacterial antigens, they could play a unique role in immunity to tuberculosis. We studied CD1-restricted T cells in the context of HIV infection by expanding CD4(-) T cell lines from 10 HIV-infected patients. Upon stimulation with Mycobacterium tuberculosis antigen or upon exposure to macrophages infected with M. tuberculosis, these T cell lines proliferated, produced IFN-gamma, and showed cytolytic T cell (CTL) activity against macrophages pulsed with mycobacterial antigen, findings consistent with a protective role against M. tuberculosis. Anti-CD1b antibodies abrogated T cell proliferation, IFN-gamma production, and CTL activity, demonstrating that these T cells are CD1 restricted. IFN-gamma production in response to M. tuberculosis was enhanced by antitransforming growth factor-beta in 8/10 lines, and by IL-15 in 2/10 lines. IFN-gamma production was augmented in a nonantigen-specific manner by IL-12 in 4/8 lines. When live HIV was cocultured with CD1-restricted T cell lines, p24 antigen and proviral DNA were not detected, indicating that the T cells were not infectable with HIV. Vaccination strategies aimed at activation and expansion of M. tuberculosis-reactive CD1-restricted T cells in HIV-infected patients may constitute a novel means to provide protection against tuberculosis, while minimizing the risk of enhancing HIV replication through stimulation of CD4(+) cells.